PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KELALULINTASAN DINAS PERHUBUNGAN KABUPATEN GRESIK - Muhammad, Alvin; Sukaris , Sukaris (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study uses quantitative methods and is included in the category of causal associative research. This study covers work discipline, work environment, and work motivation of traffic employees at the Gresik Transportation Agency. Saturated sampling is applied. This method is often used by researcher that want to use to draw broad conclusions with minimal errors or a relatively small population of less than ten people. Saturated sampling is also referred to as a census, which involves everyone in the population. The data source is 45 employees. Data collection was conducted using the outcomes of multiple linear regression analysis, prove that work discipline, work environment, and work motivation are proven to partially affect the performance of traffic employees at the Gresik Transportation Agency.